Measuring the impact of clinical practice guidelines on infantile hemangioma referrals. Issue 5 (31st August 2021) - Barton, Michael T.; Latour, Emile; Small, Alison; Leitenberger, Sabra; Funk, Tracy
Abstract: High‐risk infantile hemangiomas may be associated with significant patient comorbidity. The American Academy of Pediatrics published clinical practice guidelines with recommendations to refer high‐risk hemangiomas early. The results of this study suggest that these guidelines may have resulted in an earlier referral age of patients with high‐risk IH to hemangioma specialists.